Pengaruh Kesadaran Merek dan Persepsi Kualitas terhadap Komitmen Melalui Kepuasan Pelanggan dan Kepercayaan sebagai Mediator: Studi pada Konsumen Produk Avoskin - Naura Wafa Darmawan; I Made Sukresna (Faculty of Economics and Business Diponegoro University, 2025)
The rise of the digital era has significantly influenced marketing strategies in Indonesia, including in the beauty industry. This study examines the effect of brand awareness and perceived quality on consumer commitment, mediated by customer satisfaction and trust, among Avoskin product users. Using a quantitative approach, data were collected through online questionnaires from 223 Avoskin users selected via purposive sampling. Structural Equation Modeling (SEM) with AMOS was employed to analyze the direct and indirect effects among variables. Results reveal that brand awareness and perceived quality positively and significantly influence customer satisfaction and trust. Moreover, both satisfaction and trust significantly mediate their impact on consumer commitment. These findings highlight the importance of enhancing brand awareness and perceived quality to foster lasting customer satisfaction, trust, and commitment.